FAKTOR KEUANGAN DAN FAKTOR NON KEUANGAN YANG MEMPENGARUHI KETEPATAN WAKTU PUBLIKASI LAPORAN KEUANGAN PERUSAHAAN SEKTOR PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2015-2019 - Yolanda Ibrahim; Dicky Arisudhana (Jurnal Akuntansi dan Keuangan, 2021)
Timeliness of the publication of financial statements is one of the important aspects in presenting relevant information. This study aims to analyze the effect of financial factors proxied by liquidity, leverage and non-financial factors proxied by company age, public ownership on the timeliness of financial statement publications. This study uses secondary data with a sample of 38 mining companies listed on the Indonesia Stock Exchange for the period 2015 – 2019. The sampling method used is the purposive sampling method with the data analysis method in this study is logistic regression. The results of this study indicate that the age of the company affects the timeliness of financial reporting, while liquidity, leverage and public ownership do not affect the timeliness of the publication of financial statements.